2018
DOI: 10.1136/ejhpharm-2018-001520
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant and antiplatelet combined therapy in patients 75 years and over with atrial fibrillation: a prospective observational study assessing adherence to clinical guidelines

Abstract: ObjectiveAccording to current guidelines on atrial fibrillation (AF), the addition of an antiplatelet therapy to an anticoagulant for a stable vascular disease does not decrease the ischaemic hazard but increases the risk of bleeding. The aim of the study was to assess compliance of practices with existing clinical guidelines concerning the use of anticoagulant-antiplatelet combined therapy in patients 75 years and over with AF.MethodsThis prospective observational study was carried out at the University Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Therefore, the results are not comparable with our results. Minary et al found that in a French university hospital, 37 out of 93 (39.8%) patients with atrial fibrillation who were over 75 years old and used a VKA in combination with an antiplatelet agent, the antiplatelet agent should have been stopped [19]. These results are not completely comparable with our results because they only included patients over 75 years old with the indication of atrial fibrillation.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Therefore, the results are not comparable with our results. Minary et al found that in a French university hospital, 37 out of 93 (39.8%) patients with atrial fibrillation who were over 75 years old and used a VKA in combination with an antiplatelet agent, the antiplatelet agent should have been stopped [19]. These results are not completely comparable with our results because they only included patients over 75 years old with the indication of atrial fibrillation.…”
Section: Discussioncontrasting
confidence: 83%
“…Several studies have evaluated the guideline adherence in patients using antithrombotic medication [16][17][18][19]. Proietti et al and Lip et al found that in patients with atrial fibrillation, 40.9-60.6% received adequate antithrombotic treatment, 6.8-21.7% were overtreated and 52.3-17.3% were undertreated and received no antithrombotic treatment [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven decades later, warfarin is still in use as an anticoagulant [22]. In the meantime, several other coumarins with anticoagulant properties like acenocoumarol, phenprocoumon, and fluindione have been developed, and they are used in a variety of clinical settings [23][24][25].…”
Section: Historymentioning
confidence: 99%